Microwave ablation of focal hepatic malignancies regardless of size: A 9-year retrospective study of 64 patients. Issue 6 (June 2015) - Alexander, Erica S.; Wolf, Farrah J.; Machan, Jason T.; Charpentier, Kevin P.; Beland, Michael D.; Iannuccilli, Jason D.; Haas, Richard H.; Dupuy, Damian E.
Highlights: MWA appears to be a more effective treatment for larger tumors compared with RFA. Intraoperative MWA outperformed percutaneous MWA. Complications related to MWA of liver tumors were minor and self limited. Abstract: Purpose: To retrospectively evaluate the safety and efficacy of microwave ablation (MWA) as treatment for single, focal hepatic malignancies. Materials and Methods: Institutional review board approval was obtained for this HIPAA-compliant study. From December 2003 to May 2012, 64 patients were treated with MWA for a single hepatic lesion, in 64 sessions. Hepatocellular carcinoma (HCC) was treated in 25 patients (geometric mean tumor size, 3.33-cm; 95% CI, 2.65–4.18-cm; range, 1.0–12.0-cm), metastatic colorectal cancer (CRC) was treated in 27 patients (geometric mean tumor size, 2.7-cm; 95% CI, 2.20–3.40-cm; range, 0.8–6.0-cm), and other histological-types were treated in 12 patients (geometric mean tumor size, 3.79-cm; 95% CI, 2.72–5.26-cm; range, 1.7–8.0-cm). Kaplan–Meier (K–M) method was used to analyze time event data. Chi-square and correlation evaluated the relationship between tumor size and treatment parameters. Results: Technical success rate was 95.3% (61/64). Treatment parameters were tailored to tumor size; as size increased more antennae were used ( p  < 0.001), treatment with multiple activations increased ( p  < 0.028), and treatment time increased ( p  < 0.001). There was no statistically significant relationship between time to recurrence and tumor size, number of activations, number of antennae, and treatment time. At one-year, K–M analysis predicted a likelihood of local recurrence of 39.8% in HCC patients, 45.7% in CRC metastases patients, and 70.8% in patients with other metastases. Median cancer specific survivals for patients were 38.3 months for HCC patients, 36.3 months for CRC metastases, and 13.9 months for other histological-types. Complications occurred in 23.4% (15/64) of sessions. Conclusion: In our sample, tumor size did not appear to impact complete ablation rates or local recurrence rates for focal hepatic malignancies treated with MWA.